"Provide a complete, concise economic analysis of the following article…": Using outside readings to train students to answer a single question. Issue 4 (2nd October 2021) - Andrews, Thomas P.
Abstract: The author of this article discusses the extensive use and analysis of real-world situations as the core construct on which to build a course in principles of microeconomics. Building on the literature that focuses on current event readings, the goal here is to train students to be able to "do economics." The author details course content and assignments based on outside readings. Major assignments require students to provide a complete, concise economic analysis of outside readings covering real-world events. Strategies for instruction as well as assessment are included.